Church burglaries through Supreme Court rulings: sacrilege? - Duñaiturria Laguarda, Alicia (Cuadernos de Historia del Derecho, 2024)
This article analyzes how the Supreme Court qualified the crime of theft committed in churches, if it was understood as "sacrilegious" in a context of freedom of worship. It also delves into other elements that the High Court considered through the cassation appeals it ruled on between 1871 and 1907.